Relationship Between Post-traumatic Stress Symptoms and Anticipatory Grief in Family Caregivers of Patients With Advanced Lung Cancer: The Mediation Role of Illness Uncertainty - Sun, Di; Mao, Zhihui; Zhang, Xu; Li, Jiaojiao; Zhang, Lijuan (Frontiers in Psychiatry, 2022)
Objective：To explore the interrelationship between post-traumatic stress symptoms (PTSS), illness uncertainty (IU), and anticipatory grief (AG). Methods: Structural equation modeling with bootstrapping estimation was conducted using data from a convenience sample of 254 family caregivers of patients with advanced lung cancer in China. Participants were recruited from a public cancer hospital in Shenyang, China. The family caregivers completed the Impact of Events Scale-Revised, Uncertainty in Illness Scale Family Caregiver Version, and Anticipatory Grief Scale. Results: The measurement model has good reliability and validity, and the final model fit the data well. PTSS positively influenced AG (direct effect estimate= .391, p=.002). Moreover, IU was found to mediate the relationship between PTSS and AG (Indirect effects estimate= .168, p=.005). The mediating effect of IU accounted for up to 30.1% of the total effect. Conclusions: IU mediated the relationship between PTSS and AG. Healthcare professionals should continuously assess PTSS, IU and AG levels in FCs and provide effective intervention options for mitigation.